Evaluation of Government School Principals in Mafraq Governorate of the Critical Thinking Skills of Tenth Grade Students in Light of the Availability of Rooms for Talented and Distinguished Students - Hourani, Najat Abed Salem (Journal of Educational and Psychological Sciences, 2021)
The study aimed to uncover the evaluation of government school principals in Mafraq governorate of the critical thinking skills of tenth grade students in light of the availability of rooms for talented and distinguished students, and the study used the descriptive survey approach, and the tool consisted in a questionnaire of (15) items, distributed to a sample of (216) principals and principals. Of school principals in Mafraq governorate, and the results of the study indicated that the evaluation of government school principals in Mafraq governorate of the critical thinking skills of tenth grade students in light of the availability of rooms for talented and distinguished students obtained an overall average (4.03 out of 5) and an evaluation level (high), and at the level of dimensions. Comprehension skills obtained the highest average (4.12), then analysis skills with an average (4.01), and finally interpretation skills with an average (3.95), all of which had a (high) impact level, and there were no statistically significant differences in evaluating government school principals in Mafraq governorate of the critical thinking skills of tenth grade students In light of the availability of rooms for talented and distinguished students according to the study variable, gender, and based on the results, the researcher made recommendations for setting up various programs to develop students’ critical thinking.